On the Set of Fixed Points and Periodic Points of Continuously Differentiable Functions - Aliasghar Alikhani-Koopaei (International Journal of Mathematics and Mathematical Sciences)
In recent years, researchers have studied the size of different sets related to the dynamics of self-maps of an interval. In this note we investigate the sets of fixed points and periodic points of continuously differentiable functions and show that typically such functions have a finite set of fixed points and a countable set of periodic points.